Old campus-George West Graves Botanical Gardens-0001
A portion of the extensive propagating unit maintained at the botanical gardens. The latherwork at the left covers tiny plants that have just need potted. While at the extreme rear the pots on the rack contain over a score of ivy varieties. The back half of the bed in the center is used as a cold frame in which seedings are started during the Winter months, as well as, some hardy cuttings.